Determination of aerobic performance in youth soccer players: Effect of direct and indirect methods - Passoni Higino, W.; de Souza Sorroche, A.; de Mattos Falqueiro, P. G.; Suzuki Lima, Y. C.; Higa, C. L. (Journal of Human Kinetics, 2017)
This study was conducted to correlate and compare values for variables determined in indirect tests with the values determined directly in youth soccer players. The study subjects were 27 youth soccer players (age 16.77 ± 0.75 years; body mass 63.29 ± 7.37 kg; body height 174.14 ± 8.46 cm) playing in the basic categories of a first division team at the regional level of Brazilian soccer. Each subject was evaluated with the following tests: a) a treadmill test to directly determine values of VO2max and Vamax (Treadmill); b) an indirect Shuttle Run Test (SRT); c) an indirect Carminatti`s test (TCar). VO2max showed significantly different values in the Treadmill and the SRT (59.21 ± 5.88 and 50.67 ± 3.58 ml·kg-1·min-1, respectively). Similarly, values obtained for VPeak in the treadmill test and for Vamax in TCar were different from values for SRT VPeak (15.01 ± 1.10, 14.92 ± 0.87 and 12.64 ± 0.62 km·h-1, respectively). A correlation analysis showed a moderate relationship between values for VPeak TCar and VO2max determined on a treadmill (r = 0.46) and Vamax determined on a treadmill (r = 0.54). The analysis also showed a high correlation between values of VO2max determined on the treadmill and VO2max evaluated in the SRT (r = 0.69), as well as VPeak determined in the SRT and VO2max tested on the treadmill (r = 0.71), as well as between VPeak determined in the SRT and VO2max evaluated on the treadmill (r = 0.77). We concluded that the SRT underestimated values of VO2max and Vamax. Additionally, VPeak TCar showed no difference compared to Vamax, although it did show a low correlation with it. In addition the SRT, even with high correlations, did not seem to be a great predictor of aerobic fitness in youth soccer players.